STUDI EKSPLORASI BIOMORFIK SEBAGAI IDE DASAR DALAM PENCIPTAAN KARYA SENI RUPA TIGA DIMENSI - Afatara, Narsen; Prameswari, Nadia Sigi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2019)
Art is making quality work that can be enjoyed by others. The stages of making art are determined by ideas, ideas and being able to reconstruct into valuable works of art. One way to get ideas, ideas is to make observations. One object that can be used as observation is Ameba. Joan Miro and Santiago Calatrava are among the artists whose works are inspired by Amoeba or biomorphics. The purpose of this study is to find out how far artists explore and produce high-value works with Amoeba or biomorphics as the basic ideas in making art.